The mathematics of logic : a guide to completeness theorems and their applications - Kaye, Richard (Richard W.) (Cambridge University Press, 2007)
This textbook rescues students from traditional, dry and uninspiring introductory courses in logic, quickly providing context using genuine mathematical applications.